Introducción a los microprocesadores Z80 Manual - DECDFI (My University, 1982)
The load instructions move day internally between CPU registers of between CPU registers an external memory. All of instructions must specify source location from which the data is to be moved and a destination location. The source location is not altered by a load instruction. Examples of load group instructions include moves between any of the general purpose registers or to any external memory location. Others type of load instruction allow transfer between CPU registers and memory location. The exchange instructions can trade the contents of two registers.
Keywords: procesador; codes; hardware; software; Z80-CPU